PUBLIKASI DATA PASIEN COVID-19 DITINJAU DARI UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Wiwik Afifah; Amanda Raissa (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2021)
Indonesia is experiencing a health emergency, namely the Covid-19 Pandemic. The Covid-19 virus is a type of virus that causes infectious disease outbreaks which has the characteristics of transmission through droplets released by people infected with the Covid-19 virus. At the time of an outbreak with these characteristics, the public should know which subjects have been infected with the Covid-19 virus as a form of prevention so as not to be exposed to the Covid-19 Virus. However, this matter will be hampered because, as a country of law, Indonesia highly upholds human rights. So that Indonesia does not publish patient data because it is related to morals and also the privacy rights of these patients. This is certainly a dilemma in terms of handling Covid-19 because there are two interests that must be maintained, namely the interests of these patients and also the interests of confidentiality of Covid-19 patient data that must be maintained. Therefore, in this study the author will conduct a study about the publication of Covid-19 patient data based on the interests of the general public during the Covid-19 pandemic. The research method used This research will use a normative research method in which the author will review the related laws and regulations. The results of this study are that the confidentiality of patient data can be overridden under certain conditions that have been determined by law and one of them is at the time of the outbreak. So that when an outbreak occurs, patient data publication can be done on the basis of the public interest.